2018
DOI: 10.1007/s10566-018-9463-0
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Readiness for Change Among School Professionals and Its Relationship with Adoption and Reported Implementation of Mental Health Initiatives

Abstract: Readiness for change, defined as "the cognitive precursor to the behaviors of either resistance to, or support for, a change effort" (Armenakis, Harris, & Mossholder, 1993), can serve as a facilitator or barrier to dissemination of evidence-based services. Limited research has been conducted to understand the role of readiness for change in educational contexts and its relationship to the success of evidence-based school mental health (SMH) initiatives. The current study examined three community's (i.e. teache… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 43 publications
0
6
0
1
Order By: Relevance
“…Results from this study should be interpreted in the light of the participation of only one school coordinator in each participating school. Different staff members may perceive aspects of readiness differently (Hustus and Owens 2018 ) and using more respondents in each school might give a more reliable picture of the school readiness. However, getting busy teachers to respond to questionnaires is a difficult task and low teacher response rates have been found in previous Danish school-based studies, as well as a huge variation in number of teachers responding per school (Bonnesen et al 2020 ; Jørgensen et al 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Results from this study should be interpreted in the light of the participation of only one school coordinator in each participating school. Different staff members may perceive aspects of readiness differently (Hustus and Owens 2018 ) and using more respondents in each school might give a more reliable picture of the school readiness. However, getting busy teachers to respond to questionnaires is a difficult task and low teacher response rates have been found in previous Danish school-based studies, as well as a huge variation in number of teachers responding per school (Bonnesen et al 2020 ; Jørgensen et al 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Konteks di Jabodetabek, insentif untuk guru dan dana bantuan operasional sekolah adalah contoh bentuk perolehan sumber daya dari pemerintah yang diterima sekolah, sedangkan koordinasi berkala antara dinas Pendidikan dan sekolah dalam bentuk pengawasan, dan bimbingan merupakan contoh bentuk arahan yang penyampaiannya relatif terstruktur. Gambaran ini sejalan dengan hasil penelitian Hustus & Owens (2018) yang mengemukakan bahwa tingginya kesiapan melakukan upaya perubahan dipengaruhi oleh akuntabilitas prosedur yang disampaikan oleh pimpinan sekolah.…”
Section: Pembahasanunclassified
“…Readiness and degree of aligned IBC are similar IS and OBM constructs that may influence implementation of EBPs. Hustus and Owens (2018) defined readiness at the practitioner level as support for or resistence to adoption and implementation of practices. For example, Stahmer and Aarons (2009) used the EBPAS to assess pracitioners' attitudes toward use of EBPs in their programs, with the hypothesis that such attitudes may affect implementation, and Kratz et al (2019) reported that teacher attitudes did predict EBP fidelity .…”
Section: Is and Omb Conceptsmentioning
confidence: 99%